Factors that Influence Place of Delivery for Women of Reproductive Age in Narok South Sub County - Purity, Ngotiek; Kahiga, Dr. Titus; Ondora, Dr. Onyambu (American Journal of Health, Medicine and Nursing Practice, 2023)
Purpose: The main objective of this study was to explore the factors that influence the place of delivery for women of reproductive age in Narok South Sub County. Methodology: The study adapted a descriptive, cross sectional study design which focused on all women of reproductive age who delivered at home after antenatal hospital care visits in the last 24 months. The research was completed in Narok South Sub County, Narok County in Kenya. The target populace included all women with children below two years of age who gave birth at home yet attended antenatal care visits in a health facility in Narok North Sub-County. The study population included all women of reproductive age which were in the age bracket of 15 and 49 years from Narok south sub-county in Narok County. The study adapted two sampling techniques (purposive sampling and simple random sampling) first, purposive sampling was used to obtain women who have had delivered in the last 24 months and also key informants like TBAs and community elders. A sample of 30% of the targeted population was selected; this is coherent with the proposition by Mugenda and Mugenda (2009) that 30% of the population is deemed to be sufficient for statistical analysis in research. A semi structured questionnaire was utilized to gather data. The study utilized primary data only. The primary data was collected through semi structured questionnaires by visiting households with women of reproductive age who gave birth in the last 24 months in a non- hospital set up. Data was analyzed using excel and statistical package for social sciences SPSS version 22.0. Findings: The study found that emergencies during delivery are well handled in a hospital setup and will greatly improve delivery outcome, the health of the mother and baby. The extended walking distance nearest health facility, the lesser the expectation of mothers to make use of skilled and trained delivery service. The absence of trouble-free transportation service to the nearest health facility is also an essential significant convolution. Source of information on reproductive health matters and more so about pregnancy, labor, and place of delivery can highly influence decision-making on the place of giving birth. Majority of women in rural areas receive advice on reproductive health matters from their 'mothers-in-law and extended family members. When pregnant mothers attend ANC they are taught about delivery and how to prepare for it. Recommendations: County Education officers in liaison with social development officers to promote adult formal education to improve literacy levels, which will go a long way in influencing reproductive health decisions. County health management team, together with the reproductive health section to network with other relevant stakeholders to increase sensitization on utilization of hospital-based deliveries. Health education by all relevant stakeholders on the advantages of hospital delivery. Establish community health units and train community health volunteers and traditional birth attendants to be safe motherhood promoters.